Statistical Yearbook 2002-2004, Forty-ninth Issue - United Nations Department of Economic; Social Affairs (United Nations, 2006)
This annual compilation of statistics for over 200 countries and areas of the world is organized in four parts: world and region summary; population and social statistics; economic activity; and international economic relations. This issue of the Yearbook presents 81 tables in the fields of demographic and social statistics, national accounts, finance, labour force, wages and prices, agriculture, manufacturing, transport and communication, energy, environment, science and technology, intellectual property, international merchandise trade, international tourism, balance of payments, and development assistance. In general, the data presented are those which were available as of February 2005, and whenever possible, cover the ten-year period from 1992 to 2001 or 1993 to 2003.